Superficial Zoonotic Mycoses in Humans Associated with Cattle - Marcin Piorunek; Honorata Kubisiak-Rzepczyk; Tomasz Trafas; Tomasz Piorunek (Pathogens, 2024)
Dermatophytosis in cattle is most often caused by infection with Trichophyton verrucosum (T. verrucosum), but also with Trichophyton rubrum (T. rubrum), Trichophyton mentagrophytes (T. mentagrophytes) and others, regardless of the geographical zone. The infection is transmitted through direct contact between animals as well as infected environmental elements. The human-to-human transmission of fungal infection is also possible.. This retrospective study was conducted based on a detailed analysis of the results of the mycological examination and medical documentation of 40 patients from Greater Poland, diagnosed with cattle-to-human dermatophytoses from March 2017 to November 2023. T. verrucosum accounted for 97.5% of infections and T. mentagrophytes for 2.5%; no other species of dermatophytes from cattle were found. Superficial skin mycosis in humans associated with cattle was more often diagnosed in small children and men directly engaged in cattle breeding. The dominant etiological factor of the superficial fungal skin infection was T. verrucosum, which mainly affected the scalp in children and upper limbs in adult men. In relation to the cattle population in Greater Poland, the number of cases of superficial skin mycoses among cattle breeders and their family members over the period of more than six and a half years of observation does not seem to be high.